Analisis Pendapatan dan Biaya Operasional Sebelum dan Dimasa pandemi Covid-19 (Studi Kasus Pada STIE Mahaputra Riau) - Jonnedi; Jonnedi, Jonnedi; Oemar, Fahmi; Amdanata, Donal Devi (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2023)
The emergence of the Covid-19 virus in the city of Wuhan in the state of China, since March 2020 has almost covered the entire care business sector, from MSMEs, service companies and industry to even universities. Universities in Indonesia have also experienced a decline in revenue and operational costs. One of the higher education institutions in Indonesia is the Mahaputra Riau College of Economics (STIE Mahaputra Riau). The aim of the study was to see the difference in income and operational costs of STIE Mahaputra Riau both before and during the Covid-19 pandemic. The research method uses a comparative method with a quantitative description approach. The data used is in the form of secondary data from financial reports at STIE Mahaputra Riau during the 2018–2021 period. The results showed that the income experienced by the STIE Mahaputra Riau campus both before and during the Covid-19 pandemic fluctuated every month, but in total income during the Covid-19 pandemic was higher than income before the Covid-19 pandemic with an increase of 0.30%. While the operational costs experienced by the STIE Mahaputra Riau campus both before and during the Covid-19 pandemic fluctuated every month, the total operational costs during the Covid-19 pandemic were lower compared to operational costs before the Covid-19 pandemic with a total reduction in operational costs of -6.36%. The findings from this study are that income increased during the Covid-19 pandemic due to an increase in the number of registrations in 2020 so that it affected STIE Mahaputra Riau's income, while operational costs decreased due to the implementation of online lectures.